Amine‑functionalized radiation‑grafted nylon‑6 fbers : synthesis and adsorption performance for diclofenac sodium - Sharifah Mona, Abd Aziz Abdullah; Luqman Chuah, Abdullah; Siti Nurul Ain, Md Jamil; Ting, Teo Ming; Thomas Choong, Shean Yaw (Springer Nature, 2025)
The removal of pharmaceutical contaminants from water sources remains a critical challenge due to the limited efciency and high cost of the current technologies. This study presents the development of innovative fbrous adsorbents synthesized through radiation-induced graft-copolymerization (RIGC) of glycidyl methacrylate (GMA) onto nylon-6 (Ny6) fbers. These GMA-grafted fbers were subsequently functionalized with 1,3-diaminopropane (DAP) and diethylenetriamine (DETA), resulting in the formation of DAP(GMA-g-Ny6) and DETA(GMA-g-Ny6) adsorbents. By optimizing the graft yield (%), amine functionality, and reaction time, the amine densities of 3.39 and 2.66 mmol/g were achieved for DAP(GMA-g-Ny6) and DETA(GMA-g-Ny6), respectively. The analytical techniques, including FTIR, XPS, SEM, BET, TGA, and XRD confrmed successful amine incorporation and characterized the structural changes. The preliminary adsorption experimental results demonstrated that the DAP and DETA functionalized fbers exhibited high adsorption capacities, with DAP(GMA-g-Ny6) achieving a maximum diclofenac sodium removal efciency of 99%, compared to 90% for DETA(GMA-g-Ny6). The superior performance of DAP(GMA-g-Ny6) can be attributed to its high amine density (3.00 mmol/g), which provides extensive amine group coverage on the surface of the grafted fber, thereby facilitating strong hydrogen bonding and electrostatic interactions with diclofenac sodium molecules. These fndings suggest that the amine-functionalized nylon-6 fbers synthesized through RIGC ofer a promising and efective solution for the removal of diclofenac sodium from water, highlighting their potential application in environmental remediation.